Pengembangan Edu-Ekowisata Di Obyek Wisata Alam Telaga Tambing Taman Nasional Lore Lindu - Subastian, Halil; Malik, Adam; Sudhartono, Arief (Mitra Sains, 2023)
The purpose of this study were to develop a strategy for developing the Tambing Lake Nature Tourism Object with an environmental education perspective (edu-ecotourism) for students and university students. The research was conducted through field observations, documentation and interviews which were equipped with a list of questions (questionnaires). Determination of respondents was done intentionally (purposive sampling). Furthermore, data analysis, to determine the feasibility of the Telaga Tambing Nature Tourism Object that is able to support the concept of edu-ecotourism, used the Analysis of the Operational Area for Natural Tourism Objects and Attractions (ADO-ODTWA) while to determine the strategy for developing the Tambing Lake Nature Tourism Object with environmental education perspective (edu-ecotourism) for Students and University Students using the analysis of Strenghts, Opportunities, Weaknesses, and Threats (SWOT). The results of the analysis of determining the priority strategy for the development of Telaga Tambing Nature Tourism Objects with Environmental Education/Edu-Ecotourism For Students and Students are the SO strategy, namely (1) maintenance and improvement of Edu-ecotourism-based facilities and infrastructure, (2) make conservation education tour packages for students and Students, (3) establish Conservation Cadre.